2012
DOI: 10.1002/eji.201142021
|View full text |Cite
|
Sign up to set email alerts
|

CCL25 induces α4β7 integrin‐dependent migration of IL‐17+γδ T lymphocytes during an allergic reaction

Abstract: Herein, we provide evidence that during allergic inflammation, CCL25 induces the selective migration of IL-17 + γδ T cells mediated by α 4 β 7 integrin. Intrapleural injection of CCL25 into ovalbumin (OVA)-immunized C57BL/6 mice triggered the accumulation of γδ T lymphocytes expressing CCR9 (CCL25 receptor) and α 4 β 7 integrin in the pleura, but failed to attract αβ T lymphocytes. CCL25 attracted CCR6 + γδ T cells producing IL-17 (but not IFN-γ or IL-4). OVA challenge triggered increased production of CCL25 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 68 publications
(133 reference statements)
1
45
1
3
Order By: Relevance
“…Importantly, this effect was specific to the γδ17 subset, since both αβ T cells and the remaining IL-17 − γδ T cells were still recruited despite CCL25 neutralization. Consistent with this, the exogenous provision of CCL25 attracted γδ17 cells but not IFN-γ + or IL-4 + γδ T cells, and this was associated with a selective increase in IL-17 levels in the mouse pleura [5]. In this commentary, I discuss three topics that contextualize the new findings by Costa et al [5]: first, the homeostatic versus inflammatory functions of CCL25; second, the migration of γδ T cells to sites of inflammation; and, third, the potential roles of IL-17 (and γδ17 cells) in allergic reactions.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Importantly, this effect was specific to the γδ17 subset, since both αβ T cells and the remaining IL-17 − γδ T cells were still recruited despite CCL25 neutralization. Consistent with this, the exogenous provision of CCL25 attracted γδ17 cells but not IFN-γ + or IL-4 + γδ T cells, and this was associated with a selective increase in IL-17 levels in the mouse pleura [5]. In this commentary, I discuss three topics that contextualize the new findings by Costa et al [5]: first, the homeostatic versus inflammatory functions of CCL25; second, the migration of γδ T cells to sites of inflammation; and, third, the potential roles of IL-17 (and γδ17 cells) in allergic reactions.…”
supporting
confidence: 65%
“…Interestingly, although the β-chemokines CCL3 and CCL5 were also induced in allergic pleurisy (and can mediate γδ T-cell chemotaxis in vitro), neutralization experiments showed they were not essential for γδ T-cell recruitment. Thus, only CCL2/CCR2 played a nonredundant role in γδ T-cell migration to the inflammatory site in vivo [4].An important difference between these previous studies on CCL2/CCR2 [3,4] and the current one on CCL25/CCR9 [5] is that, while the former showed an impact on total γδ T-cell numbers, the latter only affects specifically the γδ17 subset. Thus, whereas CCR2 seems to be a determinant for γδ T-cell migration as a whole, CCR9 may be selective for γδ17 cells.…”
mentioning
confidence: 71%
“…2), typically associated with lymph node homing. Furthermore, CCL25 and CCL27, previously shown to control gd T cell migration under homeostatic or inflammatory conditions (24,33), were also equally expressed in WT and TCRd-deficient mice (Supplemental Fig. 2).…”
Section: Ccr2 Ligands Accumulate Inmentioning
confidence: 78%
“…2). Recently, members of our team have shown that CCL25 and its receptor CCR9 control the migration and lung recruitment of a subset of gd T cells committed to IL-17 production in a model of allergic pleurisy (33). In fact, the effect of CCL25 was selective to IL-17 + gd cells-namely, not extending to IFN-g-producing gd T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation